Validity of Physics Mobile Learning Media Edupark of Bayangsani South Coast Fluid on Fluid Material for High School Students Using the Android Studio Application - Adek Wulandari; - Hamdi (PILLAR OF PHYSICS EDUCATION, 2020)
This study aims to produce a mobile learning media using an android studio application based on edupark physics waterfall Bayangsani Pesisir Selatan on fluid material for high school students and find out the validity level. This type of research is development research using the Plomp model. The data source of this study was a validator team consisting of three lecturers from the Department of Physics Faculty of Mathematics and Natural Sciences UNP. The research instrument used in this study was an initial observation questionnaire for students and teachers, as well as a validation instrument. The data analysis technique used in this research is descriptive statistical techniques. Based on the results of data analysis that has been done, it can be concluded that the mobile learning media using android studio applications based on edupark physics has a validity value of 82.43 with a very valid category. The validity of the characteristics of this media product is assessed in terms of material substance, learning design, display (visual communication), and software utilization